Nonmetallic posterior monosegmental cervical fusion of a dislocated C6/7 fracture in a 4-year-old girl: a case report - Adler, Daniel; Al Mansour, Haidara; Akbar, Michael (Der Orthopäde, 2019)
Pediatric cervical spine injuries constitute approximately 1-2% of all pediatric trauma cases. Usually pediatric vertebral injuries appear as stable A type fractures, whereas B and C type injuries are relatively uncommon. In contrast to adults, the appropriate treatment strategy in children is still controversial and places spine surgeons in complex situations. This article reports the case of a 4-year-old girl with an unstable B type injury at the C6/7 level (AOSpine C6-7: B2 [F4 BL, C7:A1]) with bilateral locked fractures of the facet joints after falling down a flight of stairs.
Gesehen am 25.06.2020